2020
DOI: 10.1007/s00705-020-04842-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a microchip electrophoresis-based, high-throughput PCR-RFLP method to type Tax 233 variants of bovine leukemia virus in Japan

Abstract: Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL). We used microchip electrophoresis in combination with automatic image analysis to develop a novel high-throughput PCR-RFLP to type the gene sequences that encode BLV Tax 233. This method revealed that 233L-Tax is more prevalent than 233P-Tax in cattle in Japan. The proportion infected with BLV carrying the gene encoding 233L-Tax was significantly higher in Holstein cattle than in Japanese Black cattle. Holsteins infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Moreover, almost all BLVs infecting Hol cattle carry L233-Tax, whereas the viruses infecting JB cattle possess both forms of Tax equally [7,17]. The purpose of this study was to investigate the characteristics of EBL among JB cattle with a focus on Tax harbored in the tumors and the relation with Hol cattle.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, almost all BLVs infecting Hol cattle carry L233-Tax, whereas the viruses infecting JB cattle possess both forms of Tax equally [7,17]. The purpose of this study was to investigate the characteristics of EBL among JB cattle with a focus on Tax harbored in the tumors and the relation with Hol cattle.…”
mentioning
confidence: 99%
“…It was reported that most viruses detected in Hol cattle possessed L233-Tax nationwide [7,17] and that the prevalence of BLV was higher in dairy cows than in beef cattle [15]. A significant number of farms fatten JB cattle together with JB-Hol crossbred cattle and Hol beef cattle, and ET is widely conducted in Japan, especially in dairy areas.…”
mentioning
confidence: 99%
See 3 more Smart Citations